Standardised mortality rate for cerebrovascular diseases in the Slovak Republic from 1996 to 2013 in the context of income inequalities and its international comparison - Beáta Gavurová; Viliam Kováč; Tatiana Vagašová (Health Economics Review, 2017)
Non-communicable diseases represent one of the greatest challenges for health policymakers. The main objective of this study is to analyse the development of standardised mortality rates for cerebrovascular disease, which is one of the most common causes of deaths, in relation to income inequality in individual regions of the Slovak Republic. Direct standardisation was applied using data from the Slovak mortality database, covering the time period from 1996 to 2013. The standardised mortality rate declined by 4.23% in the Slovak Republic. However, since 1996, the rate has been higher by almost 33% in men than in women. Standardised mortality rates were lower in the northern part of the Slovak Republic than in the southern part. The regression models demonstrated an impact of the observed income-related dimensions on these rates. The income quintile ratio and Gini coefficient appeared to be the most influencing variables. The results of the analysis highlight valuable baseline information for creating new support programmes aimed at eliminating health inequalities in relation to health and social policy.
Keywords: 330; Standardised mortality rate; Cerebrovascular diseases; Income inequality; Regional disparities; the Slovak Republic